Analisis Pemanfaatan Limbah Terak Nikel (Slag) sebagai Bahan Baku Pembuatan Shotcrete dan Penanganan Limbah Lumpur Nikel (Slurry) untuk Mengurangi Dampak Pencemaran Lingkungan - Ardhymanto Am Tanjung; Rahul Gonzales; Azizah Seprianti; Rahma Izati (LPPM Institut Teknologi Petroleum Balongan, 2022)
There are 21 million tons of nickel deposits in Indonesia, which produced 800,000 tons in 2019. Theamount of nickel waste has increased because of the high nickel production rate. Both liquid and solid by-products of nickel processing, slurry, and slag, are created. The amount of tailings slurry produced annually in Indonesia is up to 25.6 million tons, compared to 13 million tons of nickel slag. Nickel slag can be recycled since it contains valuable metals, including nickel, cobalt, and copper. The chemical composition of 70% nickel slag is 41.47% Silica, 30.44% Ferric Oxide, and 2.58% Alumina. An inventive solution to replace components of shotcrete with nickel slag was discovered through literature research. On the other hand, some businesses intend to use a technology to tackle the slurry nickel, known as